Trend Analysis for the Cooling Period for Sea Water Temperatures in Aegean and Mediterranean Coasts - Eyüp Şişman (Doğal Afetler ve Çevre Dergisi)
In trend studies, classical approaches such as regression analysis and frequently used Mann-Kendall (MK) methods are bound to lose their usage due to their limitations and assumptions, due to their inability to meet their requirements in terms of binding conditions and knowledge. In order to use the regression approach for the trends and to obtain correct results, the data should fit into normal distribution, there is no internal dependency (autocorrelation), the measurements are accurate, equal variance, linearity acceptances should be investigated before each analysis. There are similar difficulties in the Mann-Kendall method, which results in no trend, increasing or decreasing trend insufficiency in engineering practices. In this study, the trends in Sea Surface Temperature (SST) and their mathematical structures are examined. The trends in different stations are compared with the suggested model. SST was recorded at four stations between 1960 and 2009.The increasing trend towards the period of 2000-2009 shows itself. The trends during of 2000-2009 period is especially striking for the Mediterranean region. However, when the model graphs are examined, there are decreasing trends that emerged in 4 different durations (1970-1979, 1980-1989, 1990-1999, 2000-2009) compared to the 1960-1969 duration, which was selected as the reference year. Depending on the reality of climate change, the neutrality of the observed data 1960-1969 should be questioned.